Crime and Public Transportation: A Case Study of Ottawa's O-Train System - Gallison, Jordana K. (Canadian journal of criminology and criminal justice, 2017)
The following research seeks to provide insight into the phenomenon of crime and public transit systems. We utilize a case study, the O-Train in Ottawa, to determine whether the presence of an O-Train station predicts crime in the surrounding neighbourhood. Crime data were obtained from the Ottawa Police Service between January 2006 and December 2006 to help identify potential clustering of offences in close proximity to the O-Train stations. Geo-spatial measures (e.g., local Moran’s I) were used to help determine whether certain offences were more prominent in areas that hosted an O-Train station, and we then used this outcome variable in a logistic regression. Our results show that the presence of an O-Train station is related to an increase in theft of vehicle, but not to robbery or commercial burglary.